Bacteriome Signature in SARS-CoV-2-Infected Patients Correlates with Increased Gut Permeability and Systemic Inflammatory Cytokines - Larissa S. Souza; Alexandre S. Ferreira-Junior; Pedro C. Estella; Ricardo K. Noda; Lhorena F. Sousa; Miguel T. Y. Murata; Lucas A. L. Carvalho; João L. Brisotti; Daniel G. Pinheiro; Josias Rodrigues; Carlos M. C. B. Fortaleza; Gislane L. V. de Oliveira (Microorganisms)
The COVID-19 pandemic has highlighted the complex interplay between the gut microbiota and systemic immune responses, particularly through the gut–lung axis. Disruptions in gut microbial diversity and function—commonly referred to as dysbiosis—have been increasingly implicated in the pathogenesis of SARS-CoV-2 infection. In this study, we assessed the gut bacteriome and permeability in SARS-CoV-2-infected patients using 16S sequencing and ELISA assays, respectively. We also measured blood inflammatory cytokines and fecal secretory IgA to evaluate systemic and mucosal immune responses. Significant alterations in both alpha and beta diversity metrics were observed in patients with COVID-19 (n = 79) and those with post-COVID-19 condition (n = 141) compared to the controls (n = 97). Differential abundance and taxonomic analyses revealed distinct microbial profiles in the infected groups. Increased plasma levels of IL-2, IL-6, IL-17A, IFN-γ, and zonulin were detected in patient samples. Some genera were elevated during acute infection, which was positively correlated with C-reactive protein, while Enterobacteriaceae and Escherichia-Shigella were associated with increased zonulin levels, indicating compromised intestinal barrier function. These findings suggest that gut dysbiosis may contribute to bacterial translocation and systemic inflammation. Overall, our results highlight the importance of the gut–lung axis and suggest that modulating the gut microbiota could support immune regulation in SARS-CoV-2 infection.